WILLIAM SHAKESPEARE IS ABRILLIANT PLAYWRIGHT OF THE GOLDEN AGE OF DRAMA - ISAQOVA SARVINOZXON BURXON QIZI; ZOIROVA DILFUZA XAYRIDDINOVNA (TADQIQOTLAR.UZ, 2024)
Abstract: This article regarded William Shakespeare as one the greatest writer in the English language, is a towering figure of the Golden Age of Drama. His profound understanding of human nature, complex characters, poetic language, and innovative storytelling made him a pivotal figure during this period of cultural flourishing, and his influence endures today.